A Conversation with David Liebman in Paris - Dely, Carole; Liebman, David (Sens public)

(untitled) (Département des littératures de langue française, 2011)
David Liebman was born in Brooklyn, New York on September 4, 1946. He began classical piano lessons at the age of nine and saxophone by twelve. His interest in jazz was sparked by seeing John Coltrane perform live in New York City clubs such as Birdland, Village Vanguard and Half Note. He is considered a renaissance man in contemporary music with a career stretching over forty years. He has played with many of the masters including Miles Davis, Elvin Jones, Chick Corea, John McLaughlin, McCoy Tyner and others. The day after a concert in duet with Marc Copland at the Sunset Jazz Club in Paris (6 December 2011), David Liebman and Carole Dely, a saxophone player and a philosopher, met to speak about jazz.